2020
DOI: 10.1080/00313831.2020.1739132
|View full text |Cite
|
Sign up to set email alerts
|

Social Excursions During the In-between Spaces of Lessons. Students’ Smartphone Use in the Upper Secondary School Classroom

Abstract: In this article, we focus on smartphone use initiated by students during lessons, with the aim of deepening the knowledge of when and why this use happens. Our methodological approach is video-ethnographic. The empirical data consists of 20 focus students in 9 upper secondary school classes, comprising 70 h of video material. The results show that the use of smartphones most often occurs in what we call the inbetween spaces during lessons. These spaces are individual and negotiated within the classroom interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The finding that obligations to peers were a key driver of the need to remain reachable by smartphone at all times, supports the findings of others (Allaby & Shannon, 2020;Toh et al, 2019). The description of the 'domino effect' of off-task activity in class being prompted by peers appears not to have been previously reported in the literature, but it could be applied to explain Olin-Scheller et al's (2021) description of a sequence of smartphone interactions among a group of students as they wait for instructions (see p. 621). Additionally, this could be an example of the role of descriptive norms as a determinant of the intention to cyberloaf in the classroom (Taneja et al, 2015).…”
Section: Peer Influencesupporting
confidence: 84%
See 3 more Smart Citations
“…The finding that obligations to peers were a key driver of the need to remain reachable by smartphone at all times, supports the findings of others (Allaby & Shannon, 2020;Toh et al, 2019). The description of the 'domino effect' of off-task activity in class being prompted by peers appears not to have been previously reported in the literature, but it could be applied to explain Olin-Scheller et al's (2021) description of a sequence of smartphone interactions among a group of students as they wait for instructions (see p. 621). Additionally, this could be an example of the role of descriptive norms as a determinant of the intention to cyberloaf in the classroom (Taneja et al, 2015).…”
Section: Peer Influencesupporting
confidence: 84%
“…Two recent video ethnographic studies are worthy of particular note as they use video recordings of classroom activities, combined with device screen recordings, to investigate natural classroom use of digital devices including smartphones. In a study of 18-19-year-old students' classroom smartphone use in Sweden, Olin-Scheller et al (2021) found that while student-initiated smartphone use was primarily for off-task social media interactions, most use was limited to periods of low teaching intensity and was smoothly integrated into the "inbetween spaces" (p.628) within the flow of a lesson. The authors acknowledge the possibility that social pressure to keep connected may lead students to create opportunities during class to engage with their smartphones and that there may be some associated cognitive costs that the study did not address (Olin-Scheller et al, 2021).…”
Section: Extent Of Digital Distraction In the Classroommentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, changes that occur in the in-between space can affect students' personal development (Bhabha, 1996;Dai, 2020;Dai and Hardy, 2021). Vilsmaier and Lang (2015) and Olin-Scheller et al (2021) also pointed out that students look for feedback and support for sustainability learning in the in-between spaces. The complicated transition processes of moving from community college to university space may create turbulent pathways for transfer students.…”
Section: Literature Reviewmentioning
confidence: 99%